Effects of cationic and anionic surfactants on the adsorption of toluidine blue onto fly ash - CANTÜRK TALMAN, REMZİYE YEŞİM (ELSEVIER SCIENCE BV, 2006)
The adsorption of cationic dye toluidine blue (TB) onto fly ash has been studied from aqueous solution, in the presence of cationic surfactant cetyl pyridinium chloride (CPC) and anionic surfactant sodium dodecyl sulfate (SDS) at three different temperatures. Two-step adsorption isotherms are observed for TB adsorption in aqueous solution. Isotherm shape is also preserved in the presence of CPC. The equilibrium saturation adsorption capacities of fly ash for TB decreased in the presence of CPC as a result of the competitive adsorption for the same sites between the same charged dye and surfactant molecules. Four-region adsorption isotherms are obtained in the presence of SDS. The adsorption of the cationic dye at low SDS concentration is enhanced by adsolubilization phenomenon because of the favorable interaction with the negatively charged adsorbed micelles. Above the critical micelle concentration free micelles are formed, TB is distributed between the free and the adsorbed aggregates, and therefore the global adsolubilization decreases. The order of changing of Freundlich isotherm constant (n) gives information about isotherm shape whether two-step or four-region adsorption isotherm. Adsorption isotherms of SDS and CPC in aqueous solution have also been constructed for interpreting adsorption results of TB in the presence of surfactants. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: toluidine blue; fly ash; cetyl pyridinium chloride; sodium dodecyl sulfate; adsorption isotherms; CRITICAL MICELLE CONCENTRATION; GEL WATER INTERFACE; LOW-COST ADSORBENTS; METHYLENE-BLUE; WASTE-WATER; AQUEOUS-SOLUTIONS; IONIC SURFACTANTS; FULLERS EARTH; RHODAMINE 3B; BASIC-DYES